Do Assessments Drive Learning? Exploring Nursing Students’ Perceptions and Study Approaches: A Cross-Sectional Study - Alnaeem, Mohammad; Suleiman, Khaled (Quality Advancement in Nursing Education / Avancées en formation infirmière)

(untitled) (Canadian Association of Schools of Nursing / Association canadienne des écoles de sciences infirmières, 2026)
Background: Students’ perceptions of assessment quality can significantly shape their learning behaviors. Understanding this relationship is especially critical in nursing education, where assessment plays a pivotal role in achieving program learning outcomes.Purpose: This study aimed to examine the relationship between undergraduate nursing students’ perceptions of assessment quality and their approaches to learning in a Jordanian private university undergoing ACEN accreditation.Methods: A cross-sectional study was conducted using validated questionnaires: the Students’ Perceptions of Assessment Quality Questionnaire (SPAQQ) and the Approaches to Learning and Studying Inventory (ALSI). A total of 645 students participated. Pearson correlation and multiple regression analyses were used to explore associations between six assessment quality dimensions and five learning approaches.Results: All six SPAQQ dimensions showed strong positive correlations with deep, surface, and strategic learning approaches (r = 0.48–0.78; p < .001). Multiple regression analyses revealed that the perceived credibility, authenticity, and effects of assessment significantly predicted deep learning (R² = 0.61), monitoring studying (R² = 0.50), organized studying (R² = 0.40), and effort management (R² = 0.42). The interpretation of test scores and credibility were significant predictors of surface learning (R² = 0.37).Conclusion: Students’ positive perceptions of assessment quality—particularly its credibility and relevance—are strongly linked to deeper and more strategic learning. These findings highlight the importance of enhancing assessment practices to foster meaningful learning, particularly in institutions seeking international accreditation.